2017
DOI: 10.1055/s-0037-1606597
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival after Salvage Surgery for Local Failure after Definitive Chemoradiation Therapy for Locally Advanced Non-small Cell Lung Cancer

Abstract: SLS in patients with locally advanced non-small cell lung surgery following dCRT is feasible, prolongs long-term survival and allows local tumor control. Selection criteria remain undefined and patients should be considered surgical candidates during multidisciplinary team conference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Where reported, mediastinal lymph node dissection was performed in a varying number of patients; 14/24 (58%); 5 ‘routinely performed’; 7 all patients had lymph nodes resected but number of stations varied between one and eight (median four); 8 18/18 (100%) with varying extent; 9 8/8 (100%) 10 based on pN staging reported for all patients; ‘all patients’ underwent radical lymphadenectomy with systematic node dissection; 11 ‘all lung resections were followed by systematic hilar and mediastinal lymph node dissection’. 12 Where reported, the incidence of pathologically confirmed N2 disease in the resection specimen was 3, 7 8, 12 13, 8 21 5 and 50%. 10 In addition, some patients who had stage IV disease prior to CRT or salvage surgery were included: the incidence was 3, 11 8, 5 8, 12 13 7 and 14%.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Where reported, mediastinal lymph node dissection was performed in a varying number of patients; 14/24 (58%); 5 ‘routinely performed’; 7 all patients had lymph nodes resected but number of stations varied between one and eight (median four); 8 18/18 (100%) with varying extent; 9 8/8 (100%) 10 based on pN staging reported for all patients; ‘all patients’ underwent radical lymphadenectomy with systematic node dissection; 11 ‘all lung resections were followed by systematic hilar and mediastinal lymph node dissection’. 12 Where reported, the incidence of pathologically confirmed N2 disease in the resection specimen was 3, 7 8, 12 13, 8 21 5 and 50%. 10 In addition, some patients who had stage IV disease prior to CRT or salvage surgery were included: the incidence was 3, 11 8, 5 8, 12 13 7 and 14%.…”
Section: Resultsmentioning
confidence: 95%
“… 12 Where reported, the incidence of pathologically confirmed N2 disease in the resection specimen was 3, 7 8, 12 13, 8 21 5 and 50%. 10 In addition, some patients who had stage IV disease prior to CRT or salvage surgery were included: the incidence was 3, 11 8, 5 8, 12 13 7 and 14%. 6 There were two patients in one study who had adjuvant chemotherapy for N2 disease found on pathological examination of the resected specimen.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations